Pagsibol ng himig nurturing the musical creativity of women and female-identifying underground musicians through a gendered approach in music training and performance venues - Fulo, Vianney Lois T.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
As the visibility of women and female-identifying musicians in the local underground music scene increases, new perspectives must emerge to transform how the space is experienced. Music infrastructure, such as performance and training spaces, must foster creativity while also adapting to meet the needs of both the target demographic and the public without becoming stagnant or constrained by conventional interpretations of a 'music space'. Hence, this study aims to holistically explore the ways in which gendered creative spaces and an application of the Musical Creativity Model (Burnard, 2012) could improve the experience within music spaces by increasing accessibility, fostering individual creativity, and challenging the typical denotations of training and performance venues. By applying the principles of gendered spaces and examining the nature of musical creativity in spatial development, this study finds that blending the formal (theaters and recording rooms) with the informal (busking areas and adaptable hallways), while enhancing the adaptability of the space, encourages the public to engage with the space more freely. Using the musical principle of syncopation-which emphasizes rhythm, disruption, and unexpected accents-the project aims to explore the intersection of music and architecture, creating a space where both aspiring and established musicians, along with their audiences, can engage with full accessibility and a deep respect for creativity and individuality.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Gender identity -- Music; Music and architecture; Women musicians